A history of land tenure in the Herschel district, Transkei - Viedge, Bronwen Elizabeth (Rhodes University, Faculty of Humanities, Department of Sociology, 2001)
A historical review of land tenure systems implemented in the Herschel district, Eastern Cape, South Africa and an analysis of the strengths and weaknesses of each system in conjunction with international experience of land tenure provide guidelines as to what elements could be incorporated in the formulation of a new integrated land tenure system. These guidelines together with the information obtained from a questionnaire survey amongst the Herschel population provide the government of South Africa with a broad outline of an integrated land tenure system that could serve to link the former homelands to the land tenure system that currently operates in the rest of the country thereby removing one of the obstacles to rural development and land redistribution.
Keywords: Land tenure -- South Africa -- Transkei; Land tenure -- Herschel -- South Africa -- Transkei; Land tenure -- History -- Herschel -- South Africa -- Transkei